Predictive Impact of Mucinous Tumors on the Clinical Outcome in Patients with Poorly Differentiated, Stage II Colon Cancer: A TOSCA Subgroup Analysis. (13th January 2020) - Rosati, Gerardo; Galli, Fabio; Cantore, Maurizio; Bergamo, Francesca; Banzi, Maria; Zampino, Maria Giulia; Mattioli, Rodolfo; Cardellino, Giovanni Gerardo; Ronzoni, Monica; Di Bartolomeo, Maria; Tamberi, Stefano; Marchetti, Paolo; et al.
Abstract: Background: Although American Society of Clinical Oncology and European Society for Medical Oncology guidelines have identified the negative prognostic factors that clinicians have to consider when treating their patients with stage II colon cancer (CC), the role of histological subtype is controversial. Subjects, Materials, and Methods: The randomized, multicenter, phase III TOSCA trial compared 3 versus 6 months of fluoropyrimidine‐oxaliplatin adjuvant chemotherapy in 3, 759 patients with high‐risk stage II or stage III CC. The objective of this substudy was to evaluate the influence of histological subtypes on the impact of the treatment duration of adjuvant chemotherapy in terms of relapse‐free survival (RFS) and overall survival (OS) in 85 mucinous adenocarcinoma (MUC) and 389 nonmucinous adenocarcinoma (NMUC) patients with high‐risk stage II, grade 3 CC. Results: A significant interaction between treatment duration and histology was observed in both RFS ( p = .027) and OS ( p = .017). In the subgroup of patients with MUC, worse RFS (adjusted hazard ratio [HR], 3.95; 95% confidence interval [CI], 1.03–15.17; p = .045) and OS (HR, 9.56; 95% CI, 1.14–79.98; p = .037) were detected for patients treated in the 3‐month arm. No statistically significant differences were found in the subgroup of patients with NMUC. Conclusion: Patients with MUC, grade 3, stage II CC require special attention and may need 6 months of oxaliplatin‐based chemotherapy. Larger studies are required to assess the combined use of histology and other prognostic/predictive factors to define the administration of chemotherapy in patients with stage II CC and to improve their prognosis. Implications for Practice: Although ASCO and ESMO guidelines define the prognostic factors for patients with stage II colon cancer to establish the use of adjuvant chemotherapy, the influence of histological subtypes is controversial in this population. This study underscores that patients with grade 3 mucinous adenocarcinomas may need adjuvant chemotherapy with oxaliplatin and fluoropyrimidines for a duration of 6 months rather than 3 months. Abstract : The role of histological subtype in patients with colon cancer undergoing adjuvant chemotherapy is unclear. This article evaluates the influence of histological subtypes, namely mucinous or non‐mucinous adenocarcinoma, on the effect of treatment duration.